OPTIMASI KEUNTUNGAN PENJUALAN MINUMAN MENGGUNAKAN PROGRAM LINEAR METODE GRAFIK (Studi Kasus: Kantin Kampus USN Papua) - Nabila Andini Putri; Heru Sutejo, Jessica Salzabilla Wayoi, Nurlinda, Habel Kapani, Yanpit Rumbiak, Noak Rematobi (Jurnal Ekonomi dan Bisnis, 2026)
This research aims to optimize the daily profit of the USN Canteen by determining the most effective sales combination of its two best-selling instant beverage products, namely Jasjus and Good Day Coffee. The main problem faced by the canteen management is the reliance on conventional intuition in daily production planning, which often results in stock shortages or inefficient use of resources due to operational constraints such as raw material availability, service time, and production capacity. The methodology applied in this study is quantitative operational research using the Linear Programming approach, which is specifically solved through the Graphical Method, an optimization technique suitable for problems involving two decision variables. The results of the graphical analysis successfully transform operational constraints into linear mathematical inequalities, forming a feasible solution region. The optimal corner point obtained from the analysis indicates the most appropriate combination of Jasjus (x) and Good Day Coffee (y) to maximize daily profit. In conclusion, the implementation of this mathematical model enables canteen management to shift from an intuition-based approach to a data-driven decision-making strategy, thereby improving daily profit planning and operational efficiency.